Human Intruder Detection using MANET Technology - Ilias, Irma Syarlina Che; Azmi, Mohammad Khairy (International Journal of Engineering and Technology, 2018)
This study focus on MANET as a sensor based system to manage security on the designated area. MANET is a continuously self-configuring, infrastructure-less network of mobile devices connected without wires. MANET is relatively a new technology which people can use it to eradicate missing hardware in computer lab issues. By using MANET it can help us to know the location where there is the activity happen which then we can prevent the activity earlier. In addition, this study using Arduino Uno, a low cost and ARM-based computer on a small circuit board which can detect hardware movement up to 8 meters. Furthermore, o notification on intrusion are through the buzzer. Besides, the technology able to monitor voice, record the footage of intruder, controlling light switch and view room temperature from mobile phone. Therefore, this study can be considering valuable and can be commercialized.